Pendampingan Metode Pembalajaran Kewirausahaan Dengan Sistem Bisnis Model Canvas Pada SMAIT Ruhul Islam Simeulue - Damrus, Damrus; Maulida Sari, Cut Devi; Zhafira, Nabila Hilmy; Chairiyaton, Chairiyaton; Manan, Afni Abdul (Jurnal Pengabdian Agro and Marine Industry, 2023)
The rapid development of information technology raises demands on various fields, including entrepreneurship. This demand is especially addressed to the younger generation or novice businessmen who are the initial target. It is hoped that with the emergence of various demands and activities that support business development for beginners, it can reduce the unemployment rate. The importance of changing mindsets and providing the right strategy for novice business people is important to do. One effort that can be done is to increase understanding and mastery of advances in information technology, especially to face global competition. Therefore it is important to carry out various trainings and activities that can support creativity as well as new and unique ideas for these novice businessmen, which are currently mostly carried out by students. The training conducted at SMAIT Ruhul Islam was carried out in order to build an entrepreneurial spirit for students at a young age and to have interest and basic knowledge about entrepreneurial planning using the business model canvas. SMAIT Ruhul Islam Simeulue students can practice making a business model canvas and can apply various approaches to the business model canvas for the progress of their respective businesses.